Sustainability analysis of skipjack tuna catch based on multidimensional scaling (MDS) in the coastal area of Pasuruan Regency - Munir, Misbach; Misbah, Achmad (AGROMIX, 2025)
Introduction: Indonesian tuna production holds significant economic value, yet Pasuruan Regency experienced a drastic decline from 21,391 tons in 2018 to only 467 tons in 2020. This downturn is attributed to multiple factors including deteriorating seawater quality, constrained distribution channels, price volatility, and various socio-environmental challenges. Issues such as potential overfishing, reliance on middlemen, and insufficient fisheries management further compromise the industry's sustainability. Methods: This study employed the RAPFISH technique, utilizing Multidimensional Scaling (MDS), to assess the sustainability of the tuna fishery across four key dimensions: ecological, economic, social, and institutional. Primary data collection involved surveys and interviews with principal stakeholders (fishers, collectors, micro-enterprises), complemented by secondary data analysis from relevant fisheries institutions to evaluate long-term trends. Results: The assessment indicated a 'fairly sustainable' overall status for the Pasuruan tuna fishery, although revealing considerable vulnerabilities and variations among stakeholders. Key challenges identified include ongoing environmental degradation, unstable market conditions, and socio-economic dependencies limiting fishers' long-term stability. Leverage analysis pinpointed critical factors with the highest impact on sustainability, primarily social aspects , economic factors, and market responsiveness. Conclusion: The moderate sustainability level necessitates targeted strategies focused on the identified leverage points. Enhancing work safety, fostering collaboration, improving operational cost management, and increasing customer responsiveness are crucial. These targeted actions, combined with improved resource management practices and stronger institutional support, offer the most promising pathway to ensure the long-term viability and resilience of the skipjack tuna fisheries sector in Pasuruan Regency.